Leiomiossarcoma cutâneo no tronco Cutaneous leiomyosarcoma on the trunk - Marisa Carpinteiro André; Joana Veiga Antunes; Miguel Duarte Reis; Paulo Leal Filipe; Luís Miguel Soares de Almeida (Sociedade Brasileira de Dermatologia, 2011)
O Leiomiossarcoma cutâneo é um tumor maligno que representa 7% dos sarcomas dos tecidos moles, afetando, mais frequentemente, homens entre os 50-70 anos. A localização, no tronco, é atípica, constituindo 10 a 15% dos casos. A radioterapia e o traumatismo prévio têm sido referidos como fatores de risco. Descrevemos um homem de 57 anos, com tumor eritemato-violáceo, indolor, de consistência dura, localizado na região pré-esternal, com cerca de oito meses de evolução. A histopatologia evidenciou tumor maligno de células fusiformes, com núcleos em forma de "charuto", pleomórficos, com alto índice mitótico, ocupando toda a espessura da derme. Estas células expressaram actina do músculo liso, desmina e vimentina e foram negativas para proteína S-100 e pancitoqueratina. Foi efetuada a exérese cirúrgica radical do tumor. Cutaneous leiomyosarcoma is a relatively uncommon tumor that accounts for 7% of all soft tissue sarcomas. It occurs more frequently in males between 50-70 years and only 10-15% of cases are located on the trunk. Radiotherapy and previous trauma have been implied as risk factors. We report the case of a 57 year-old male with an eight-month history of a hard painless erythematous-violaceous tumor on the presternal region. Histopathology evidenced a malignant spindle cell tumor, "cigar" shaped, with pleomorphic nuclei and a high mitotic index that occupied the entire dermal thickness. Immunohistochemical staining of the tumor cells was positive for smooth muscle actin, desmin and vimentin and negative for S-100 protein and pan-cytokeratin, which supported the diagnosis of dermal leiomyosarcoma. Radical surgery was performed to remove the tumor.